Objetivo de leitura e processo de compreensão leitora - Borges, Caroline Bernardes (2018)
This master's thesis aims to contribute to the psycholinguistic studies regarding the relationship between the reading objective and the process of reading comprehension, investigating how the reading comprehension process of high school students varies as their learning objectives are also changed. Associated with other reading variables, such as the reader's previous knowledge and the properties of the read text, the reading objectives are responsible for conducting the comprehension process. In this way, the characteristics of this process are evidenced (Kato, 1999; Giasson, 2000; Solé, 1998; Smith, 2003), being understood as an important cognitive activity that includes comprehension, reading procedures, strategies of reading and linguistic awareness. The sample of the study was composed of 91 subjects (1st year high school students) from a public school in Porto Alegre. A single text was selected - from which a survey of students' previous knowledge regarding their subject was carried out - and three different tasks were suggested for students before reading (a task for each group of students). Each group then had a different reading objective to be achieved (group 1/ reading objective 1: produce a summary, group 2/reading objective 2: searching a specific information, group 3/reading objective 3: proposing solutions to the problems exposed in the text). Soon after, the students responded to a verbal protocol through which they explained the procedures they performed to develop the task and expressed their level of linguistic awareness about the activity performed. Thus, the changes that occurred during this process due to the different objectives could be verified through the explanations given by the subjects. The results showed: positive correlation between previous knowledge and reading comprehension in all reading objectives; comprehension by reading the full text in objectives 1, 2 and 3; help of re-reading the text in the understanding in objective 2 (inverse in objective 3); assistance of support in various segments of the text in the understanding in objective 1 (inverse in objectives 2 and 3); positive correlation between comprehension and linguistic awareness in all reading objectives. These results confirm that the reading objectives influence the comprehension process as they show that different procedures were adopted for each objective, as well as contributing in different ways to the comprehension.